JOURNAL OF GOVERNMENT & POLITICS : Personal Branding of Anies Baswedan Through facebook And Twitter Account: Study Of Image Grid Analysis in Banjarmasin Society Aged 17-24 years - Ramadhan , Febrian Anshari (FISIPOL UMY, 2016)
This research aimed was the grid of personal branding image of Anies Baswedan through facebook and Twitter account on Banjarmasin society.